Performance evaluation of the Roche Elecsys Anti-SARS-CoV-2 S immunoassay - Riester, Elena; Findeisen, Peter; Hegel, J. Kolja; Kabesch, Michael; Ambrosch, Andreas; Rank, Christopher M.; Pessl, Florina; Laengin, Tina; Niederhauser, Christoph (Journal of virological methods, 2021)
•The Elecsys® Anti-SARS-CoV-2 S assay detects antibodies to the SARS-CoV-2 S protein.•This assay demonstrated an overall specificity of 99.95% (7876/7880 samples).•Overall sensitivity for this assay was 97.92% (235/240 samples).•Performance was comparable to or greater than that of other commercial assays.•This assay can reliably identify past exposure to SARS-CoV-2 in various populations. The Elecsys® Anti-SARS-CoV-2 S immunoassay (Roche Diagnostics International Ltd, Rotkreuz, Switzerland) has been developed for the detection of antibodies to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike (S) protein. We evaluated the assay performance using samples from seven sites in Germany, Austria, and Switzerland. For specificity and sensitivity analyses, 7880 presumed negative pre-pandemic samples and 827 SARS-CoV-2 PCR-confirmed single or sequential samples from 272 different patients were tested, respectively. The overall specificity and sensitivity (≥14 days post-PCR) for the Elecsys Anti-SARS-CoV-2 S immunoassay were 99.95% (95% confidence interval [CI]: 99.87–99.99; 7876/7880) and 97.92% (95% CI: 95.21–99.32; 235/240), respectively. The Elecsys Anti-SARS-CoV-2 S immunoassay had significantly higher specificity compared with the LIAISON® SARS-CoV-2 S1/S2 IgG (99.95% [2032/2033] vs 98.82% [2009/2033]), ADVIA Centaur® SARS-CoV-2 Total (100% [928/928] vs 86.96% [807/928]), ARCHITECT SARS-CoV-2 IgG (99.97% [2931/2932] vs 99.69% [2923/2932]), iFlash-SARS-CoV-2 IgM (100.00% [928/928] vs 99.57% [924/928]), and EUROIMMUN Anti-SARS-CoV-2 IgG (100.00% [903/903] vs 97.45% [880/903]) and IgA (100.00% [895/895] vs 95.75% [857/895]) assays. The Elecsys Anti-SARS-CoV-2 S immunoassay had significantly higher sensitivity (≥14 days post-PCR) compared with the ARCHITECT SARS-CoV-2 IgG (98.70% [76/77] vs 87.01% [67/77]), iFlash-SARS-CoV-2 IgG (100.00% [76/76] vs 93.42% [71/76]) and IgM (100.00% [76/76] vs 35.53% [27/76]), and EUROIMMUN Anti-SARS-CoV-2 IgG (98.26% [113/115] vs 93.91% [108/115]) assays. Therefore, the Elecsys Anti-SARS-CoV-2 S assay demonstrated a reliable performance across various sample populations for the detection of anti-S antibodies.